Assistance for Adolescents in Preventing Stunting During the First 1000 Days of Life through the Formation of 'REDAKZI PENTING' (Health and Nutrition-Aware Adolescents Caring for Stunting) in Tambak Oso Waru Village, Sidoarjo - Ika Mustika; Esti Novi Andyarini; Moch. Irfan Hadi (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Stunting is one of the nutrition problems that is a national priority today. Stunting occurs as a result of a lack of nutritional intake, recurrent infectious diseases and inadequate family factors or psychosocial factors, especially in the first 1000 days of life. Adolescents, as prospective parents, will give birth to the next generation and need to have adequate knowledge about health, nutrition and stunting so that nutritional deficiencies do not occur, especially in the first 1000 days of life. This community service activity aims to improve the knowledge, attitudes and behaviour of adolescents in preventing stunting, especially in the first 1000 days of life, through the formation of the